Decision-Making and Vocational Information - Vu-Thu-Huong, Catherine (Canadian Journal of Counselling and Psychotherapy, 2012)
Presented in this article is the rationale on Career Information and Career Education. With the expansion of world modern technology, career development has become very important in guidance. In educational institutions, the Information Service of a guidance programme is fulfilled by the Career Information Library. Illustrated in this article is a classification system based upon the Dictionary of Occupational Titles and the Standard Industrial Classification Manual.